Protective coatings for complex organic flexible materials I: characterization and tribological performance of TiO2 and ZnO films deposited by magnetron sputtering on cork - B. Tiss; D. Martínez-Martínez; C. Mansilla; J.R. Gomes; C.S. Abreu; N. Pereira; L. Cunha (Applied Surface Science Advances)
The escalating imperative to combat the climate change has generated sustainability trends, leading to a rising demands for eco-friendly products. Cork and rubber are versatile materials based or derived from natural sources with various industrial uses and applications. This work represents the first part of a comprehensive investigation focusing on cork, with rubber being the subject of a subsequent paper. Cork shows unique properties which make it attractive for many applications beyond wine stoppers, such as bags, flooring, walls lining and aerospace components. Nevertheless, cork suffers from strong wearing when subjected to friction and mechanical wear. The objective of this work is to improve the tribological performance of cork by deposition of a protective oxide layer, while preserving its original appearance. As such, optically transparent TiO2 and ZnO thin films were deposited onto silicon and cork substrates using magnetron sputtering. The TiO2 thin films exhibited an amorphous structure while the ZnO films displayed texture along the (002) direction of hexagonal wurtzite structure of zinc oxide. ZnO-coated cork showed lower coefficient of friction against 100Cr6 stainless steel balls than uncoated cork, while TiO2 coatings did not reveal any relevant improvement. The wear rate of the samples was evaluated using a novel method based on the analysis of energy dispersive spectra. All coated samples demonstrated an improvement regarding wear resistance, although ZnO films seem to be more effective, in line with the reduction of friction coefficient up to 38 % respect uncoated cork. The detection of metallic oxide coatings within the wear track after the tribotests indicates a strong adhesion of both coatings to the cork substrate, which is supported by tensile tests.